A novel Fe-free photo-electro-Fenton-like system for enhanced ciprofloxacin degradation: bifunctional Z-scheme WO3/g-C3N4. Issue 9 (5th August 2019) - Bai, Xiaoyu; Li, Yi; Xie, Liangbo; Liu, Xiaohui; Zhan, Sihui; Hu, Wenping
Abstract : Antibiotics accumulate because of their extensive use and difficult degradation, which can lead to the formation of novel antibiotic resistant genes and bacteria, which can cause damage to human health and the ecological environment. Abstract : Antibiotics accumulate because of their extensive use and difficult degradation, which can lead to the formation of novel antibiotic resistant genes and bacteria, which can cause damage to human health and the ecological environment. Here, we designed a novel photo-electro-Fenton-like (PEF-like) system with bifunctional Z-scheme WO3 /g-C3 N4 for accelerated decomposition and enhanced mineralization of stubborn ciprofloxacin (CIP). This PEF-like system, accompanied by visible light activation, with the optimal WO3 /g-C3 N4 (1 : 6) composite exhibited outstanding removal efficiency of CIP compared with a single photocatalysis system and electro-Fenton-like (EF-like) system, and the elimination rate reached 100% within 2 h under visible light irradiation. The WO3 /g-C3 N4 (1 : 6) composite displayed the strongest visible light absorption, the weakest recombination of electron–hole pairs, the highest photocurrent response and the lowest electrochemical impedance compared with pristine WO3 and g-C3 N4 . Significantly, WO3 /g-C3 N4 (1 : 6) played a dual role in the PEF-like system which could not only produce ˙OH, ˙O2 − and h + during photocatalysis, but could also generate ˙OH through the reactions of W 5+ and photoexcited electrons of g-C3 N4 for the decomposition of H2 O2 . It was worth noting that this bifunctional PEF-like catalyst with photoelectric synergy could replace Fe 2+ in a conventional electro-Fenton reaction and the pH range was broadened while still maintaining efficient degradation efficiency in the range of 2–9. The PEF-like system maintained a high elimination rate of CIP after five consecutive runs which revealed that it possessed prominent stability and feasibility.